MODEL PERILAKU ANGGOTA KLUB MOTOR DI BENGKAYANG: PENDEKATAN EKSPLORATORIS - Pramatatya Resindra Widya; Aloysius Hari Kristianto; Jimmi Jimmi (JURNAL MANEKSI, 2020)
The aim of this study is to explore the antecedents and consequences of people’s intention to join the brand community. Nowdays, brand community has become a new marketing channel for marketers to enter the market. This exploratory research conducted with Qualitative methods with ethnography approach and some motorbike clubs  as the participant. This research found a new concept of behavioral models in brand community and it can be use for behavioral sciences studies especially in consumer behavior.